Sikap Peduli Santri Terhadap Lingkungan Pondok Pesantren di masa Pendemi Covid-19 - Dandi yansyah; Ida Farida; Andewi Suhartini (Program Pascasarjana IAIN Langsa, 2021)
Abstrack: The purpose of this study was to determine the students' caring attitude towards the Islamic boarding school environment during the COVID-19 pandemic and to determine the validity and reliability of attitude measurement instruments. This research uses a descriptive method. Researchers used a Likert scale to critically measure three indicators of students' attitudes about students' awareness, thinking, and wise attitudes. Furthermore, 34 statement items and four answers were made for respondents, namely strongly agree, agree, disagree, and strongly disagree. The validity and reliability of the questions were calculated using SPSS 26. The results of this study showed that the students' caring attitude towards Islamic boarding schools during the COVID-19 pandemic was categorized as good with a score of 8.2. Keywords: Attitude, Environment & The Covid-19 Pandemic